2015
DOI: 10.1212/wnl.0000000000001582
|View full text |Cite
|
Sign up to set email alerts
|

White matter hyperintensities in middle-aged adults with childhood-onset type 1 diabetes

Abstract: Objective: Although microvascular complications are common in type 1 diabetes mellitus (T1DM), few studies have quantified the severity, risk factors, and implications of cerebral microvascular damage in these patients. As life expectancy in patients with T1DM increases, patients are exposed to age-and disease-related factors that may contribute to cerebral microvascular disease.Methods: Severity and volume of white matter hyperintensities (WMH) and infarcts were quantified in 97 middle-aged patients with chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 41 publications
4
56
1
Order By: Relevance
“…Increased presence of cerebral small vessel disease such as white matter hyperintensities and lacunes have been reported among individuals with T1DM (mean age 50 years) (57,58); however, other studies among older T1DM patients (mean age ~60 years and with known microvascular complications) (59) have reported no significant differences in white matter lesions or microinfarcts compared with control subjects. While we cannot exclude the possibility that occult cerebrovascular disease may also contribute to the differences observed in the T1DM-Unaware individuals, this appears less likely given our participants had well-controlled diabetes, had no history of cerebrovascular disease or cardiovascular disease, and were significantly younger (mean age 30 and 40 years for T1DM-Aware and -Unaware, respectively) than the groups reported in the literature.…”
Section: Methodsmentioning
confidence: 98%
“…Increased presence of cerebral small vessel disease such as white matter hyperintensities and lacunes have been reported among individuals with T1DM (mean age 50 years) (57,58); however, other studies among older T1DM patients (mean age ~60 years and with known microvascular complications) (59) have reported no significant differences in white matter lesions or microinfarcts compared with control subjects. While we cannot exclude the possibility that occult cerebrovascular disease may also contribute to the differences observed in the T1DM-Unaware individuals, this appears less likely given our participants had well-controlled diabetes, had no history of cerebrovascular disease or cardiovascular disease, and were significantly younger (mean age 30 and 40 years for T1DM-Aware and -Unaware, respectively) than the groups reported in the literature.…”
Section: Methodsmentioning
confidence: 98%
“…As previously described, WMH had no parenchymal loss, nor showed central suppression on the T2/FLAIR. 3 In addition, severity of WMH was visually rated using the Fazekas scale, with possible scores of 0 (no WMH/normal), 1 (mild), 2 (moderate) and 3 (severe). 19 As we have previously shown, none of these T1D participants were free of WMH; hence, Fazekas scores in this population ranged from 1 to 3.…”
Section: Neuroimagingmentioning
confidence: 99%
“…19 As we have previously shown, none of these T1D participants were free of WMH; hence, Fazekas scores in this population ranged from 1 to 3. 3 …”
Section: Neuroimagingmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that patients with T1DM have an increased risk of lacunar stroke (Luitse et al 2012) and those with additional microangiopathy had decreased structural connectivity in posterior brain regions (van Duinkerken et al 2012a) and impaired function in the ventral attention network (Van Duinkerken et al 2012b). However, the effect of vascular lesions on the cognitive decline in T1DM patients is not entirely clear Nunley et al 2015;Biessels and Reijmer 2014;Huang et al 2014). In contrast to T2DM, T1DM begins earlier in life and may influence brain development (Biessels et al 2008;de Felice and Benedict 2015) via insulin receptors in the hypothalamus, which play a key role in the memory system (De Felice et al 2014;de Felice and Benedict 2015).…”
Section: Introductionmentioning
confidence: 99%